2009
DOI: 10.1510/icvts.2008.192872
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of the modified single-patch technique in complete atrioventricular septal defect

Abstract: We examined the usefulness of the modified single-patch technique for the surgical management of complete atrioventricular septal defect (AVSD). Sixty-one patients undergoing total correction for complete AVSD from January 1997 to December 2006 were classified to the modified single-patch technique group (18 patients) and the classical one-/two-patch technique group (43 patients). The surgical outcomes of the modified single-patch technique were compared with those of the classical-patch technique. Aortic cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…Although modified single‐patch repair technique was reported to have the advantage of relative simplicity and shorter ischemic time, several previous reports comparing the outcomes of different surgical techniques for the repair of CAVSD showed no differences in residual septal defects, degree of postoperative LAVVR, need for reoperation, or duration of postoperative intensive care unit and hospital stays 16‐18 . Similarly, both in our first group (Group I) and in the second group (Group II) there were no significant differences in regard to postoperative intensive care unit and hospital stays between patients operated on using different surgical techniques (Table 3).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Although modified single‐patch repair technique was reported to have the advantage of relative simplicity and shorter ischemic time, several previous reports comparing the outcomes of different surgical techniques for the repair of CAVSD showed no differences in residual septal defects, degree of postoperative LAVVR, need for reoperation, or duration of postoperative intensive care unit and hospital stays 16‐18 . Similarly, both in our first group (Group I) and in the second group (Group II) there were no significant differences in regard to postoperative intensive care unit and hospital stays between patients operated on using different surgical techniques (Table 3).…”
Section: Discussionmentioning
confidence: 50%
“…In this group, the mean age at repair was 9.4 ± 5.0 months, whereas overall mortality and reoperation rate was 26.6% (12 patients) and 13.3% (six patients), respectively 5 . Ages at repair, mortality, and reoperation rates of this group were significantly high with respect to the current literature 16‐18 . However, after August 2006 (Group II) our patient selection criteria evolved clearly, and the mean age at repair decreased to 5.2 ± 3.1 months in six years.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Overall, the outcomes in both groups were similar; however, the Nunn technique was simpler with shorter ischemic times. Despite this, the authors expressed concern that this technique may not be applicable for those with large VSD and associated TOF or valve abnormalities (27).…”
Section: Tof and Double Outlet Right Ventricle (Dorv)mentioning
confidence: 99%
“…Besides simplifying the surgery, it was demonstrated that eliminating the VSD patch has the advantage of better coaptation of the left AV valve by lowering the implantation level of the valve to the crest of the interventricular septum. [2,3,6] We were able to practice this method with success even in our older patient group who had a large VSD and thickened valves, and none of our patients had more than mild residual AV valve regurgitation after repair. In addition, this method is easier to perform on low-weight patients due to their flexible tissues, as we experienced in four patients weighting less than five kilograms.…”
Section: Discussionmentioning
confidence: 79%